Anatomy of the floral nectaries of selected species of Gardenieae (Rubiaceae) - Judkevich, Marina Daniela (2022)
Rubiaceae is one of the five most species-rich families of Angiosperm, its flowers are characterized by a nectariferous disc surrounding the base of the style; however, there are almost no studies on anatomy of these structures in the family. The aim of this study was to describe for the first time the anatomy of the floral nectaries in the tribe Gardenieae (Rubiaceae). Flowers from Cordiera concolor, Genipa americana, Randia calycina, Randia ferox, Randia heteromera, Randia micracantha, and Tocoyena formosa were collected, photographed, and processed using conventional techniques for observation with optical and scanning electron microscopies. In all species the nectary is differentiated histologically into epidermis, nectary and sub-nectary parenchyma, and vascular bundles. Nectar is exuded via nectarostomata. The nectaries have reproductive function, and are structural and mesenchymal during the floral stage. Whereas after corolla has fallen they are persistent nectaries, with post-floral secretion and extranuptial function. In addition, floral visitors that appeared on open flowers and after corolla fall were recorded.